2015
DOI: 10.1097/mcp.0000000000000167
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mesothelin and fibulin-3 in pleural fluid and serum as markers in malignant mesothelioma

Abstract: To date, soluble mesothelin remains the best available biomarker for mesothelioma and a positive result is clinically useful in patients with pleural effusions in whom the diagnosis is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
(26 reference statements)
1
17
0
Order By: Relevance
“…CD163 + on macrophages), extracellular matrix proteins (e.g. OPN, fibulin-3) and RNA/DNA levels and sequence [56][57][58][59][60]. Although the majority of nucleic acid biomarkers have not yet gained acceptance in clinical practice, analysis of epidermal growth factor receptor (EGFR), EML4-ALK and KRAS mutations have a valid role for the targeted treatment of patients with lung cancer.…”
Section: Biomarkersmentioning
confidence: 99%
“…CD163 + on macrophages), extracellular matrix proteins (e.g. OPN, fibulin-3) and RNA/DNA levels and sequence [56][57][58][59][60]. Although the majority of nucleic acid biomarkers have not yet gained acceptance in clinical practice, analysis of epidermal growth factor receptor (EGFR), EML4-ALK and KRAS mutations have a valid role for the targeted treatment of patients with lung cancer.…”
Section: Biomarkersmentioning
confidence: 99%
“…Recent findings have documented the significantly altered expression status of humoral fibulin-3 in mesothelioma, thereby highlighting its promising application as a novel biomarker for MPM diagnosis and prognosis [918]. Nevertheless, single study often presented with inaccurate and insufficient information due to restrictions from limited sample size and research programs.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, serum mesothelin has been reported, for the first time, as a prognostic marker in MPM: high soluble mesothelin level significantly correlates with shorter survival, leading to a poor prognosis (12). Its prognostic value has been strongly debated: many following studies confirmed this association (13-15) but others did not endorse serum mesothelin prognostic significance (26,87). While a recent meta-analysis performed on 579 MPM patients further corroborates the inverse association of serum SMRP concentration with the OS (16).…”
Section: Clinical Implications Of Overexpressed Genes In Mpmmentioning
confidence: 77%
“…In order to better characterize the sensitivity and specificity of SMRP as a biomarker for MPM it should take in consideration that SMRP performance as diagnostic biomarker could be influenced by genetics variants, as show in the recent work by De Santi et al (30) and SNP located in the promoter or in the 3'UTR of MSLN gene could affect protein expression levels (89). SMRPs diagnostic value has been evaluated also in pleural effusion (25,26,29) and it has been observed a higher diagnostic performance in pleural effusion than in serum assessment (22). The need to detect the MPM at the early stages led several authors to investigate whether mesothelin can contribute towards the evaluation of the carcinogenic risk in populations exposed to asbestos: high level of SMRPs have been proposed as a marker for early diagnosis in combination with two epigenetic marker (27) or alone (28).…”
Section: Clinical Implications Of Overexpressed Genes In Mpmmentioning
confidence: 99%